2006
DOI: 10.1292/jvms.68.421
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Detection of Mdm2 and p53 in Feline Mammary Gland Tumors

Abstract: ABSTRACT. The objective of this study was to evaluate nuclear reactivity of Mdm2 and p53 proteins by immunohistochemical means in feline mammary gland tumors; 12 adenomas which included 6 adenomatous lesions obtained from the tissue adjacent to adenocarcinomas, and 22 adenocarcinomas. Seven adenomas and 18 adenocarcinomas showed moderate or marked Mdm2 reactivity. Sixteen adenocarcinomas showed moderate to marked p53 reactivity, but 9 adenomas showed none. Discordant Mdm2 overexpression was found in 5 adenomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The same reaction was run on slides with primary antibodies omitted as negative control, feline mammary adenocarcinoma was used as positive control for p53 antibody 21 .…”
Section: Methodsmentioning
confidence: 99%
“…The same reaction was run on slides with primary antibodies omitted as negative control, feline mammary adenocarcinoma was used as positive control for p53 antibody 21 .…”
Section: Methodsmentioning
confidence: 99%
“…[47][48][49] Different immunohistochemical protocols, scoring systems, and the absence of a standardized cutoff value for p53 positivity may be responsible for this variability. 62,64,66,67,80 In one study with follow-on data, there was no association between p53 mutations and 1-year postsurgical survival. 80 Furthermore, no significant correlation has been found between p53 expression and histologic grade, ER status, Mdm2, cyclin A, cyclin D, TopBP1 (topoisomerase IIb binding protein 1), and HER-2 expression (Table 1).…”
Section: Histochemical and Immunohistochemical Parametersmentioning
confidence: 96%
“…80 Furthermore, no significant correlation has been found between p53 expression and histologic grade, ER status, Mdm2, cyclin A, cyclin D, TopBP1 (topoisomerase IIb binding protein 1), and HER-2 expression (Table 1). 62,66,80 Standardization of the IHC protocol and scoring system and more extensive follow-up studies are required to evaluate the role of p53 in FMCs.…”
Section: Histochemical and Immunohistochemical Parametersmentioning
confidence: 99%
“…64 Protein p53 mutation and nuclear accumulation has been detected immunohistochemically in 18.9% of feline mammary carcinomas, and it was shown that p53 immunohistochemical reactivity was significantly lower in adenomas compared with adenocarcinomas. 63,65 Other studies demonstrated overexpression of p53 in 32.5-33% of carcinomas. 66,67 RON Macrophage-stimulating protein receptor (RON) is a member of the family of receptor tyrosine kinases that stimulate invasive properties of carcinoma cells.…”
Section: Protein P53mentioning
confidence: 99%